Role of Pharmacists in Hormonal Contraceptive Access: A Survey of North Carolina Pharmacists - Gwen J Seamon; Allison Burke; Casey R Tak; Amy Lenell; Macary Weck Marciniak; Mollie Ashe Scott (MDPI AG, 2020)
The role of pharmacy in healthcare continues to evolve as pharmacists gain increased clinical responsibilities in the United States, such as the opportunity to prescribe hormonal contraception. Currently, North Carolina (NC) pharmacists do not have this ability. While previous research focused on the perceptions of community pharmacists surrounding this practice, no previous research surveyed all pharmacists in a state. This cross-sectional, web-based survey was distributed to all actively licensed pharmacists residing in the state of NC in November 2018. The primary objective was to determine the likelihood of NC community pharmacists to prescribe hormonal contraception. Secondary outcomes included: evaluation of all respondent support and perceptions of this practice as advocacy occurs on the state organization level and unified support is critical; opinions regarding over-the-counter (OTC) status of contraception; and potential barriers to prescribing. Overall, 83% of community pharmacists were likely to prescribe hormonal contraception. No differences in likelihood to prescribe were detected between geographic settings. Community pharmacists reported that the most common barriers to impact prescribing were added responsibility and liability (69.8%) and time constraints (67.2%). Fewer than 10% of respondents felt that hormonal contraception should be classified as OTC (7.9%). Noncommunity pharmacists were significantly more likely to agree that prescribing hormonal contraception allows pharmacists to practice at a higher level, that increased access to hormonal contraception is an important public health issue, and that rural areas would benefit from pharmacist-prescribed hormonal contraception. Overall, this study found a willingness to prescribe and support from the majority of both community and noncommunity pharmacists. Limitations of the study included a low response rate and potential nonresponse bias. Future research is needed to address solutions to potential barriers and uptake of this practice, if implemented.